Applications and Techniques in Information Security 5th International Conference, ATIS 2014, Melbourne, VIC, Australia, November 26-28, 2014. Proceedings - Batten, Lynn.; Li, Gang.; Niu, Wenjia; Warren, Matthew; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
This book constitutes the refereed proceedings of the International Conference on Applications and Techniques in Information Security, ATIS 2014, held in Melbourne, Australia, in November 2014. The 16 revised full papers and 8 short papers presented were carefully reviewed and selected from 56 submissions. The papers are organized in topical sections on applications; curbing cyber crimes; data privacy; digital forensics; security implementations.
Applications -- Curbing cyber crimes -- Data privacy -- Digital forensics -- Security implementations.
Keywords: Computer science; Computer security; Data encryption (Computer science).; Computer Science; Systems and Data Security; Data Encryption; Electronic books